Wireless power transfer and harvesting for IoT and robotics applications - Huang, Chengwei (Nanyang Technological University, 2022)
Traditional power supply cords have become less important because they prevent large-scale utilization and mobility. In addition, the use of batteries as a substitute for power cords is not an optimal solution because batteries have a short lifetime, thereby increasing the cost, weight, and ecological footprint of the hardware implementation. Their recharging or replacement is impractical and incurs operational costs. Recent progress has allowed electromagnetic wave energy to be transferred from power sources (i.e., transmitters) to destinations (i.e., receivers) wirelessly, the so-called wireless power transfer (WPT) technique. New developments in the WPT technique motivate new avenues of research in different applications. Recently, WPT has been used in mobile phones, electric vehicles, medical implants, and wireless sensor networks. This dissertation focuses on far-field microwave wireless power transformation for robotics and IoT applications. Firstly, it compares different techniques in WPT system and tells the merits of using microwave. Then, key components of the microwave WPT harvesting system (receiver) are introduced, including principle of rectifier and diode, matching circuit and low-pass filter. The procedures to design these components are also mentioned. Finally, the whole circuit of the receiver is designed using ADS. The whole circuit in this dissertation use a two-branch configuration which includes two types of rectifying diode with two different threshold voltage. And the performance of three matching networks is tested. In the matching circuit of main rectifier diode D1, S11 has minimum value -17.134dB when frequency is 2.45GHz. In sub-branch of rectifier D2, S11 is -3.8dB in RF part when frequency is 2.45GHz, but it also can pass some RF signal. While S11 in DC part is 0dB and S21 is -34.243dB when frequency is 2.45GHz, which mean DC part can block RF signal and only pass DC signal in this part. Overall, the whole rectifier has a satisfying matching circuit and the power range of the receiver is enhanced due to the application of two-branch design.